SRIWIJAYA MOTORCYCLE SECURITY: SISTEM KEAMANAN SEPEDA MOTOR MENGGUNAKAN PASSWORD BERBASIS MIKROKONTROLER ATMEGA8535 - Aprillisianti, Adelia; Yara, Galuh Diantie; Setiawan, Hendra (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Nowadays, people prefer to choose motorcycle as their transportation. But, security of motorcycle isnât enough to protect the motorcycle from being stolen. Therefore, this program is called Sriwijaya Motorcycle Security (SMS) to find out working system and excellence of SMS. Manufacture of SMS is started by simulation program using Proteus 7. It was performed to create program using C language with compiler code vision AVR, to run microcontroller ATMega8535. After the simulation is running perfectly, the preparation of the prototype and the implementation at motorcycle were carried out. Without entering password, the motorcycle is useless and cannot be run. This product is expected to reduce the rate of motorcycle being stolen.